ІНСТРУМЕНТИ ЗМІЦНЕННЯ БЮДЖЕТНОЇ СТІЙКОСТІ ТЕРИТОРІАЛЬНИХ ГРОМАД В УМОВАХ НЕСТАБІЛЬНОСТІ: ПРАКТИЧНІ АСПЕКТИ (Світ фінансів, 2025)
Вступ. Російсько-українська війна спровокувала безпрецедентні наслідки для економічного розвитку як України загалом, так і її територіальних громад зокрема. Спричинила безпрецедентну економічну, соціальну та гуманітарну кризу, яка, своєю чергою, посилила фінансову нестабільність та знизила стійкість соціально-економічних систем на різних рівнях. Тому питання вдосконалення інструментів зміцнення бюджетної стійкості громад у сучасних умовах потребують наукових досліджень.Мета – виявити сучасні проблеми порушення бюджетної стійкості територіальних громад та обґрунтувати інструменти її зміцнення в умовах надмірної невизначеності.Результати. Виявлено: зміни у структурі доходів місцевих бюджетів, спричинені зменшенням надходжень від ключових податків та вилученням військового ПДФО, що призвело до фінансових дисбалансів і загострення соціально-економічних проблем; зниження темпів приросту власних доходів місцевих бюджетів; посилення трансфертної залежності місцевих бюджетів від державного та скорочення капітальних видатків місцевих бюджетів. Зважаючи на обмежені можливості формування фінансових ресурсів територіальних громад в сучасних умовах, наголошено на важливості бюджетної складової формування фінансового потенціалу громад в умовах нестабільності. Запропоновано напрями зміцнення бюджетної стійкості територіальних громад в частині: зміни механізму горизонтального вирівнювання податкоспроможності місцевих бюджетів; вдосконалення механізму адміністрування місцевих податків і зборів та посилення контролю за їх надходженнями; покращення ефективності використання активів, якими розпоряджаються громади; розмежування повноважень між органами виконавчої влади та органами місцевого самоврядування за принципом субсидіарності. Introduction. The Russian-Ukrainian war has provoked unprecedented consequences for the economic development of both Ukraine and its territorial communities. The war in Ukraine has triggered an unprecedented economic, social and humanitarian crisis, which in turn has increased financial instability and reduced the resilience of socio-economic systems at various levels.The purpose of the article is to identify the current problems of violation of the budgetary sustainability of territorial communities and to substantiate the tools for its strengthening in the face of excessive uncertainty.Results. The article discusses the problems of ensuring the budgetary sustainability of territorial communities of Ukraine in the context of a war economy and excessive uncertainty. The author identifies the following: changes in the structure of local budget revenues caused by a decrease in revenues from key taxes and the withdrawal of military personal income tax, which led to financial imbalances and aggravation of socio-economic problems; a decrease in the growth rate of local budget revenues; increased transfer dependence of local budgets on the State budget and a reduction in capital expenditures of local budgets. Given the limited possibilities of forming financial resources of territorial communities in modern conditions, the article emphasizes the importance of the budgetary component of forming the financial potential of communities in conditions of instability. The author proposes the following ways to strengthen the budgetary sustainability of territorial communities: changing the mechanism of horizontal equalization of the tax capacity of local budgets; improving the mechanism of administration of local taxes and fees and strengthening control over their revenues; improving the efficiency of use of assets managed by communities; delimitation of powers between executive authorities and local self-government bodies on the principle of subsidiarity. The author emphasizes the need to return to the principles of fiscal balance and to restore the revenue autonomy of local self-government, as without this, communities will not be able to restore and rebuild their territories.